Determining the Ideal Type of Superior Variety as A Target for Breeding of Winged Bean - Kuswanto, Kuswanto; Yulianah, I.; Saptadi, D.; Andayani, R. D. (AGRIVITA Journal of Agricultural Science, 2024)
Breeding activities for winged bean plants (Psophocarpus tetragonolobus (L.) DC.) necessitate genetic diversity from local varieties. Identifying winged bean lines adds valuable initial information for shaping policies in plant breeding. Before proceeding with varietal development, it is crucial to establish the ideal type (ideotype) for superior winged bean varieties. The primary objective of this research is to ascertain the idiotype for superior winged bean varieties. The research was conducted in 2023 at Universitas Brawijaya, Indonesia, and involves the evaluation of five improved lines. The initial evaluation focuses on qualitative and quantitative characteristics of ideotype. The second evaluation concerns winged bean seeds' ideal morphological and physiological qualities. The third evaluation assesses winged bean pods' ideal physical and organoleptic preferences. The research outcomes have yielded the ideal morphological characteristics for winged bean varieties. This idiotype will be the foundation for the direction and target of winged bean plant breeding efforts, among the lines evaluated. NSM2 exhibits ideal flowering time and pod length characteristics, and lines PTL and PTL display ideal pod forms. MML and PBL lines have flavors aligned with market preferences regarding organoleptic qualities. These lines will be further improved through crossing to develop ideal varieties.